(untitled) (Tempo e Argumento, 2022)
During the second half of the 20th century, Latin America experienced periods of great tension and political turmoil due to numerous coups d’état orchestrated, in its vast majority, by military sectors supported, among others, by the respective US governments. This cycle was running out and, in the last decade of the 20th century, the prevailing environment in the Latin American region was the resumption of democracy. However, at the end of the first decade of the 21st century, the specter of coupism returned to Latin America after a coup d’état was carried out in Honduras with the deposition of then President Manuel Zelaya on June 28, 2009. This episode - and other coups that have taken place in other countries in the region since then -, which has raised the need for a broad reflection in relation to the current form of imperialist domination in the order of the globalization of capital, was an important agenda of the international news of the popular press vehicles alternative and generated a significant iconographic production, mainly of cartoons. In this sense, the objective of this article is to analyze the editorial cartoons produced by Carlos Latuff about the coup d’état in Honduras, through the analysis of the chargic discourse. Marked by a denunciation of the violation of democracy in that country, as well as a criticism of the partial stance of the Brazilian media in defense of the interests of the coup plotters, the editorial cartoons of Carlos Latuff’s about the episode documented and forcefully denounced the alliance between Congress, the Judiciary and the Honduran Army in carrying out the aforementioned coup d’état.